Effect of Vitamin D3 on Liver and Kidney Function of Diabetes Mellitus Male Rats - Nabeel Mahdi Abed , (University of Thi-Qar Journal of Science, 2020)
The present study was carried out in the animal house and laboratories of the College of Veterinary Medicine/ University of Basrah to investigate the role of the administration of vitamin D3 on liver and kidney function of alloxan induced toxic in mature male rats. For this purpose, 48 male rats were divided into 4 groups with 12 animals in each as the following; group (1), animals of were administered with D.W(0.2ml)/day by oral gavages for 6 weeks as control group, group(2) were injected intraperitoneally with 150 mg/kg b.w of alloxan as diabetic group, group (3) were injected with alloxan then administered with 500 UI/kg/day of alpha 25-hydroxy vitamin D3 by gavages for 6 weeks orally, group (4) were injected with alloxan then administer 1000 UI/kg/day of alpha 25-hydroxy vitamin D3 by gavages for 6 weeks orally. At the end of the experiment, animals were euthanized and blood samples were obtained for some biochemical assessment of liver and kidneys.In compares with control, alloxan treated rats recorded a significant increase (p≤0.05)in serum concentration of ALT, AST,ALP ,urea and creatinine, while there was a significant decrease (p≤0.05) in serum total protein. On other hand, administration of vitamin D3 for diabetic rats induced a significant improvement (P≤0.05) of serum ALT, AST, ALP, total protein urea and creatinine.